Development of Individual Language Ability in View of Self-Ability in Early Childhood - Lesmana, Gusman; Ramadhani, Layla Suci; Farhan, Irfan; Deliati, Deliati; Rahayu, Eni (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
The purpose of this article is to provide information related to the topic of development in children which includes physical and mental aspects. One aspect of mental development in children is language development. From an early age, children's language skills must be trained and honed properly because when used as a tool, it is basically an expression of thoughts and feelings that are carried out well, because with language people can know their needs well. Children learn language like they learn other things, namely by imitating and repeating the words used by adults. The research technique used in writing this article is literature study, namely by researching and understanding books, documents or other written sources that are relevant and support the study of language development which is supported by clarification of survey results and random field observations in Medan City. Language development in early childhood must be stimulated from an early age because the role of language is very important for human life in interacting with each other. Factors that influence language development: 1) Health, 2) Intelligence, 3) Social status, 4) Gender, 5) Family relationships.